2016
DOI: 10.1002/bit.25966
|View full text |Cite
|
Sign up to set email alerts
|

A high gas fraction, reduced power, syngas bioprocessing method demonstrated with a Clostridium ljungdahlii OTA1 paper biocomposite

Abstract: We propose a novel approach to continuous bioprocessing of gases. A miniaturized coated-paper high gas fraction biocomposite absorber has been developed using slowly shaken horizontal anaerobic tubes with concentrated Clostridium ljungdahlii OTA1 absorbing syngas as a model system. These gas absorbers demonstrate elevated CO mass transfer with low power input, reduced liquid requirements, elevated substrate consumption, and increased product secretion compared to shaken suspended cells. We concentrate OTA1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Very few studies have been reported so far on the application of trickle-bed reactors for syngas fermentation on a laboratory-scale (e.g. Bredwell et al, 1999;Yasin et al, 2015;Devarapalli et al, 2016;Schulte et al, 2016;Shen et al, 2017). High CO conversion rates of up to 91% were observed with Clostridium ragsdalei in a trickle-bed reactor with non-porous glass beads of 6 mm as carriers (Devarapalli et al, 2016).…”
Section: Bioprocess Developmentsmentioning
confidence: 99%
“…Very few studies have been reported so far on the application of trickle-bed reactors for syngas fermentation on a laboratory-scale (e.g. Bredwell et al, 1999;Yasin et al, 2015;Devarapalli et al, 2016;Schulte et al, 2016;Shen et al, 2017). High CO conversion rates of up to 91% were observed with Clostridium ragsdalei in a trickle-bed reactor with non-porous glass beads of 6 mm as carriers (Devarapalli et al, 2016).…”
Section: Bioprocess Developmentsmentioning
confidence: 99%
“…Some common biocoating deposition techniques include extrusion [34,90,91], spray drying [92], the wire wound rod drawdown Mayer rod coating method [13,67,93], 3-D ink-jet deposition [94] and the convective assembly [12,47,95]. Recently, dielectrophoresis (DEP) has also been used to generate photoreactive cyanobacteria cell monolayers on top of polyelectrolyte adhesives [96].…”
Section: Preparation Of Biocoatingsmentioning
confidence: 99%
“…PCC7002 (cyanobacterial aerobic phototroph). Investigation of C. ljungdahlii biocoated papers, coated without adhesive latex, has recently be extended by Schulte et al [91], who optimized surface area, with mass-transfer power input reduced by 3 orders of magnitude compared to traditional bioreactors and reduced liquid volume. His approach intensified the rate of CO uptake by over 17 fold.…”
Section: Example Of Environmental Applications Of Biocoatings Intensimentioning
confidence: 99%
“…Stabilization of anaerobic bacteria that are capable of assimilating single carbon gases, such as C . ljungdahlii , and other clostridia, could prove to be highly beneficial in developing bioprocess-oriented large scale gas treatment technologies [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a thin-film coating based approach of embedding the microbial samples in paper based biocomposite was undertaken [ 5 , 20 ], and a simple convective drying mechanism using inert argon gas purge technique was used for dry-processing the samples. The technique employed here is significantly different and simpler from the conventional drying modalities commonly used in the bioprocessing industry such as lyophilization and spray drying.…”
Section: Introductionmentioning
confidence: 99%